Gothic : Transmutations of Horror in Late Twentieth Century Art - The Institute of Contemporary Art Boston; Cooper, Dennis; Gianvito, John; Grunenberg, Christoph; Hannaham, James; Kalinovska, Milena; McGrath, Patrick; Oates, Joyce Carol; Rosenheim, Shawn; Toth, Csaba; Williams, Anne (Boston : Institute of Contemporary Art Boston, 1997)
Becker, Julie ; Carocci, Monica ; Chapman, Dinos & Jake ; Crewdson, Gregory ; Edmier, Keith ; Elaine, James ; Gober, Robert ; Gordon, Douglas ; Hansbauer, Wolfgang Amadeus ; Hodges, Jim ; Jamie, Cameron ; Kelley, Mike ; Lane, Abigall ; Leonard, Zoe ; Oursler, Tony ; Pepe, Sheila ; Rockman, Alexis ; Rosenberg, Aura ; Schoolwerth, Pieter ; Sherman, Cindy ; Silverthorne, Jeanne ; Simmons, Gary
biografie
Gothic : Transmutations of Horror in Late Twentieth Century Art, The Institute of Contemporary Art, Boston, April 24 - July 6, 1997
Engels
boek